2010
DOI: 10.1007/s00586-010-1653-x
|View full text |Cite
|
Sign up to set email alerts
|

Triggered electromyography for placement of thoracic pedicle screws: is it reliable?

Abstract: Reliable electromyography (EMG) thresholds for detecting medial breaches in the thoracic spine are lacking, and there is a paucity of reports evaluating this modality in patients with adolescent idiopathic scoliosis (AIS). This retrospective analysis evaluates the ability of triggered EMG to detect medial breaches with thoracic pedicle screws in patients with AIS. We reviewed 50 patients (937 pedicle screws) undergoing posterior spinal fusion (PSF) with intraoperative EMG testing. Postoperative CT scans were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 35 publications
1
40
0
3
Order By: Relevance
“…8) that were roughly comparable to or better than those from other studies. 55,60 Not only did this allow us to corroborate findings from these other studies, but we effectively had a baseline against which we could compare findings from our novel approach. Having now done this and shown that monitoring leg EMG activity is far more reliable for predicting medially malpositioned screws, we see no advantage to continuing to monitor intercostal or abdominal muscle groups going forward and have stopped this practice.…”
Section: Is There Any Benefit To Monitoring Intercostal or Abdominal mentioning
confidence: 62%
See 3 more Smart Citations
“…8) that were roughly comparable to or better than those from other studies. 55,60 Not only did this allow us to corroborate findings from these other studies, but we effectively had a baseline against which we could compare findings from our novel approach. Having now done this and shown that monitoring leg EMG activity is far more reliable for predicting medially malpositioned screws, we see no advantage to continuing to monitor intercostal or abdominal muscle groups going forward and have stopped this practice.…”
Section: Is There Any Benefit To Monitoring Intercostal or Abdominal mentioning
confidence: 62%
“…It is not clear whether stimuli were delivered to the pedicle track via a ball-tipped probe, but screw stimulation was definitely used in that study. 60 With a reported sensitivity of only 0.28 to medial defects of 2 mm or more in magnitude, 60 it is hard to argue with the conclusions of that study.…”
Section: How Do Results Of the Current Study Compare With Other Neuromentioning
confidence: 83%
See 2 more Smart Citations
“…A pesar de que la electromiografía (EMG) con tren de impulsos es una técnica aceptada para la correcta monitorización de la instrumentación transpedicular en la columna lumbar 10 , sigue existiendo controversia sobre su fiabilidad a nivel del segmento torácico 1 , si bien otros autores, como Rodríguez-Olaverri 2 , han demostrado su utilidad en la instrumentación de niveles torácicos altos.…”
Section: Discussionunclassified